Tranparansi dan Akuntabilitas Pelaporan Keuangan Masjid Agung Al-Akbar Surabaya - Ruci Arizanda Rahayu (Jurnal Reviu Akuntansi dan Keuangan, 2017)
This study is conducted to understand the meaning of transparency and accountability financialreport of Surabaya Al Akbar national Mosque. This study is a descriptive qualitative studywhile the study approach is phenomenological transcendental by taking site and location atSurabaya Al Akbar National Mosque. Data is gained by interview to 12 (twelve) informant keysas communities, donor, administrative section head, treasury, secretary, and mosque staff. Datavalidity testing is taken by triangulation technique and analysis method is taken by intentionalanalysis, epoche, and eidetic reduction steps. The result of the study concludes that Surabaya AlAkbar National Mosque in applying accountancy uses the basic standard PSAK nu. 45 year2011 about nonprofit organization including financial position report, activities report, moneysupply report, and notes for financial report. Applying this practice is guaranteed by good faithquality values as amanah, istiqomah, uswah, mas’uliah, and liljami’il-ummah as behaviororientation for the mosque organizer, skillfully human resources in organization structure, community role, and the acknowledgment by quality management system ISO 9001:2008. Accountability principal is part of worship by vertical and horizontal responsibility pattern. The verticalpattern to supervisor agency, East Java Government, and Allah SWT to get His blessing. Thehorizontal pattern is tended to mosque donor and society. Transparency principal is done byproviding clear information about the procedures, costs, and responsibility of the mosque organizer agency and giving ease access to financial report information, complaint mechanism arrangement, and improving information through cooperation with public medium. However, financial report has not checked yet by independent auditor so, it is lessening the value of accountability and transparency financial report itself.Keyword:accountability, Allah’s blessing, informant, interview, phenomenological, transparency.